Multifunctional Porous Graphene for High‐Efficiency Steam Generation by Heat Localization. (16th June 2015) - Ito, Yoshikazu; Tanabe, Yoichi; Han, Jiuhui; Fujita, Takeshi; Tanigaki, Katsumi; Chen, Mingwei
<x xml:space="preserve">Abstract</x> Multifunctional nanoporous graphene is realized as a heat generator to convert solar illumination into high‐energy steam. The novel 3D nanoporous graphene demonstrates a highly energy‐effective steam generation with an energy conversation of 80%.